Direct numerical analyses of nanoscale thermal transport near MgO edge dislocations. (September 2021) - Sekimoto, Wataru; Fujii, Susumu; Yoshiya, Masato
Abstract: We report numerical analyses to examine the impact of edge dislocation onto phonon thermal conduction in its vicinity. Two types of edge dislocations, one with open core and another with densely-packed core, show different magnitude of suppression of thermal conductivity across dislocation lines, more than crystallographic anisotropy. It is also found that small density of dislocations effectively scatters phonons lowering thermal conductivity while higher density of dislocations is less effective to suppress thermal conduction. Detailed analyses on bond strains and atomic vibrational states indicated that, while linear dependence of atomic thermal conductivity is found when bond strain is small as in elastic strain field, non-linear/anharmonic dependence of atomic thermal conductivity emerges for the highly strained and under-coordinated atoms at the cores. A combination of these leads to remarkable suppression in thermal conductivity at non-arrayed dislocations even if atoms are positioned away from dislocation core. Graphical abstract: Image, graphical abstract